2021
DOI: 10.3389/fendo.2021.634415
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury as Frequent Cause of Hypopituitarism and Growth Hormone Deficiency: Epidemiology, Diagnosis, and Treatment

Abstract: Traumatic brain injury (TBI)-related hypopituitarism has been recognized as a clinical entity for more than a century, with the first case being reported in 1918. However, during the 20th century hypopituitarism was considered only a rare sequela of TBI. Since 2000 several studies strongly suggest that TBI-mediated pituitary hormones deficiency may be more frequent than previously thought. Growth hormone deficiency (GHD) is the most common abnormality, followed by hypogonadism, hypothyroidism, hypocortisolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 183 publications
0
39
0
Order By: Relevance
“…The association between the number of other pituitary deficiencies and the probability of CAI is not surprising; in fact, the global function of the hypothalamus and pituitary gland is deeply interconnected, and the coexistence of different pituitary deficits is a feature frequently encountered in hypopituitarism [34][35][36][37][38]. Moreover, our finding that CAI was significantly associated with the presence of ≥ 3 other pituitary deficiencies, and not with a lower compromise of the pituitary function, is coherent with the notion that the ACTH secretion is one of the most resistant among pituitary ones [34][35][36][37][38]. The role of sex as a risk factor for CAI is in line with previous findings by other authors [39][40][41][42]; male sex, in fact, has been found to be associated with a higher chance of hypopituitarism in various clinical settings, even after adjustment for other concurrent predictors [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The association between the number of other pituitary deficiencies and the probability of CAI is not surprising; in fact, the global function of the hypothalamus and pituitary gland is deeply interconnected, and the coexistence of different pituitary deficits is a feature frequently encountered in hypopituitarism [34][35][36][37][38]. Moreover, our finding that CAI was significantly associated with the presence of ≥ 3 other pituitary deficiencies, and not with a lower compromise of the pituitary function, is coherent with the notion that the ACTH secretion is one of the most resistant among pituitary ones [34][35][36][37][38]. The role of sex as a risk factor for CAI is in line with previous findings by other authors [39][40][41][42]; male sex, in fact, has been found to be associated with a higher chance of hypopituitarism in various clinical settings, even after adjustment for other concurrent predictors [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The primary injury of TBI occurs directly in response to mechanical forces, like contusion, hemorrhage, hypoxia, etc. The primary injury can trigger the secondary injury that relates to several biochemical alterations, such as inflammation, nerve cell damage, and cerebral edema, contributing to exacerbating TBI progression (Alam et al, 2020;Gasco et al, 2021). Tumor necrosis factor receptor-related factor 6 (TRAF6) is a target of miR-873-5p.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Hypopituitarism results from the failure of one or more pituitary hormones to be produced or released into the circulation by the pituitary gland, leading to specific systemic effects. Anterior pituitary failure is caused by several etiologic factors, including traumatic brain injury, sellar tumors, genetic mutations, infiltrative and infectious diseases [ 6 ].…”
Section: Hypopituitarism and Pituitary Involvement In Sars-cov-2 Infectionmentioning
confidence: 99%